Laminar natural convection in saltbox roofs for both summerlike and winterlike boundary conditions - Varol, Yasin; Koca, Ahmet; Öztop, Hakan Fehmi (My University, 2006)
Saltbox roofs have trapezoidal geometry whose one wall is vertical and they have wide applications in buildings. In the present study, laminar natural convection heat transfer and fluid flow are performed in the saltbox roofs for summerlike (bottom is cold, inclined ceiling is hot) and winterlike (bottom is hot, inclined ceiling is cold) boundary conditions. In both cases, vertical wall is adiabatic. Governing equations for natural convection in streamline-vorticity form are solved using the finite difference method with successive under relaxation (SUR) technique. Numerical computations were examined for Ra = 103, 104, 105, 106, 5×106 and 107. Prandtl number is chosen as 0.71 which corresponds to air and inclination angle (18°) is chosen according to climate of Elazig, Turkey (38.7°N). Results are compared with the gable roof(triangle geometry) with the same bottom distance and observed that lower heat transfer is obtained when saltbox roof were used. © 2006 Asian Network for Scientific Information.
Keywords: Finite difference method; Heat transfer; Natural convection; Saltbox roof